2006
DOI: 10.1183/09031936.06.00101005
|View full text |Cite
|
Sign up to set email alerts
|

Allopurinol improves endothelial function in sleep apnoea: a randomised controlled study

Abstract: Increased oxidative stress in obstructive sleep apnoea is thought to contribute to endothelial dysfunction. The objective of this study was to test the hypothesis that inhibition of xanthine oxidase by allopurinol can improve endothelial function in patients with obstructive sleep apnoea. A randomised double-blind placebo-controlled crossover study was performed on 12 patients with moderate-to-severe obstructive sleep apnoea, comparing 300 mg allopurinol daily for 2 weeks with placebo. Endothelial function was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
100
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(108 citation statements)
references
References 38 publications
(37 reference statements)
5
100
0
2
Order By: Relevance
“…Previous studies reported that endothelial dysfunction in patients with OSA was reversible with administration of antioxidants (22,24). In this study, we found direct evidence of increased peroxynitrite production in the microcirculation of patients with OSA, providing an explanation for the role of antioxidants.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Previous studies reported that endothelial dysfunction in patients with OSA was reversible with administration of antioxidants (22,24). In this study, we found direct evidence of increased peroxynitrite production in the microcirculation of patients with OSA, providing an explanation for the role of antioxidants.…”
Section: Discussionsupporting
confidence: 65%
“…The mechanism of endothelial dysfunction in OSA is largely unknown. Endothelial dysfunction in OSA is reversible with antioxidants (22)(23)(24), suggesting a role for oxidant overproduction in the decreased NO availability in OSA. This provides parallels to other cardiovascular diseases in which oxidative stress-induced endothelial dysfunction is important (25,26).…”
mentioning
confidence: 93%
“…Several studies have reported an inverse relationship between uric acid and endothelial function/ FMD (13,18 -21), although this has not uniformly been noted (22). A number of studies have also reported that lowering uric acid with allopurinol may improve endothelial function in individuals with a variety of conditions, including subjects with heart failure (23-25), those with diabetes (26), heavy smokers (27), or those with obstructive sleep apnea (28). However, to our knowledge, only one study examined the effect of allopurinol on endothelial function in subjects with asymptomatic hyperuricemia (13).…”
Section: Discussionmentioning
confidence: 68%
“…However, most clinical research has studied the correlation of this impact via therapeutic interventions without analyzing causality (10,25,26). Other studies have shown improvements in oxidative stress with CPAP treatment (7,(27)(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…Malondialdehyde (MDA) is a lipid peroxidation marker, commonly used in human pathology (10)(11)(12). P-selectin is largely responsible for the rolling phase of the leukocyte adhesion cascade (13).…”
Section: Introductionmentioning
confidence: 99%